2014
DOI: 10.1186/s40560-014-0049-0
|View full text |Cite
|
Sign up to set email alerts
|

Administration of recombinant thrombomodulin before progression of disease causing disseminated intravascular coagulation might be better compared with administration after progression of disease

Abstract: Background: As disseminated intravascular coagulation (DIC) causes multiple organ failure, recombinant thrombomodulin (rTM) is widely used in Japan for treating DIC. However, the optimal timing of rTM administration has not yet been determined. We hypothesized that the administration of rTM before progression of disease causing DIC might be better for the treatment of DIC than that after progression of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…11 Several investigators have also reported that rTM administration may improve the SOFA score and reduce the mortality rate among patients with sepsis-induced DIC, 15 20 with Yatabe et al suggesting that early rTM administration is better than delayed administration after the diagnosis of DIC. 34 These findings support the early administration of rTM, which is supported by our observation of an association of rTM administration with an early improvement in the SOFA score, independent of the adequacy of initial infection control. In this context, the change in SOFA score is a useful measure for evaluating the effects of interventions on survival outcomes among critically ill patients.…”
Section: Discussionsupporting
confidence: 81%
“…11 Several investigators have also reported that rTM administration may improve the SOFA score and reduce the mortality rate among patients with sepsis-induced DIC, 15 20 with Yatabe et al suggesting that early rTM administration is better than delayed administration after the diagnosis of DIC. 34 These findings support the early administration of rTM, which is supported by our observation of an association of rTM administration with an early improvement in the SOFA score, independent of the adequacy of initial infection control. In this context, the change in SOFA score is a useful measure for evaluating the effects of interventions on survival outcomes among critically ill patients.…”
Section: Discussionsupporting
confidence: 81%
“…9 Furthermore, the JAAM DIC scoring system is able to diagnose DIC earlier than the other DIC scoring systems. 29 As early treatment with rhsTM is effective, 30 using the rhsTM strategy in combination with the JAAM DIC score is logical. However, unaffected patients are likely included if only the JAAM DIC score is used.…”
Section: Discussionmentioning
confidence: 99%